Aspectos relevantes das circunstâncias judiciais na individualização da pena - Piedade, Antonio Sergio Cordeiro (2009)
The current work aims to analyze the circumstances described in Article 59 of the Brazilian Criminal Code, checking its reach and extension in the individualization of the sentence. A historical evolution of the individualization of the sentence in Brazil will b made and it will be analyzed according to the legislative, judicial and executive plan, as well as its co-relation with other constitutional principles of the criminal law, taking the human dignity into account because this work concerns a closed legal system. If Article 59 of the Criminal Code is understood and handled in a proper way, it is considered a judicial security rule of the system and provides concretion and makes it feasible to apply the sentence individualization. The judge, however, must take all judicial circumstances into account when defining the sentence in order to fit them in the case, making his decision clear, giving a fair sanction which guarantees the citizen s rights and helps to prevent society from crime